Genomic anatomy of male-specific microchromosomes in a gynogenetic fish. - Miao Ding (Public Library of Science (PLoS), 2021)
Unisexual taxa are commonly considered short-lived as the absence of meiotic recombination is supposed to accumulate deleterious mutations and hinder the creation of genetic diversity. However, the gynogenetic gibel carp (Carassius gibelio) with high genetic diversity and wide ecological distribution has outlived its predicted extinction time of a strict unisexual reproduction population. Unlike other unisexual vertebrates, males associated with supernumerary microchromosomes have been observed in gibel carp, which provides a unique system to explore the rationales underlying male occurrence in unisexual lineage and evolution of unisexual reproduction. Here, we identified a massively expanded satellite DNA cluster on microchromosomes of hexaploid gibel carp via comparing with the ancestral tetraploid crucian carp (Carassius auratus). Based on the satellite cluster, we developed a method for single chromosomal fluorescence microdissection and isolated three male-specific microchromosomes in a male metaphase cell. Genomic anatomy revealed that these male-specific microchromosomes contained homologous sequences of autosomes and abundant repetitive elements. Significantly, several potential male-specific genes with transcriptional activity were identified, among which four and five genes displayed male-specific and male-biased expression in gonads, respectively, during the developmental period of sex determination. Therefore, the male-specific microchromosomes resembling common features of sex chromosomes may be the main driving force for male occurrence in gynogenetic gibel carp, which sheds new light on the evolution of unisexual reproduction.